On-farm experimentation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
On-farm Experimentation Handbook For Rural Development Projects / Kurt Steiner (a practical guide published jointly by) CTA and GTZ, the Technical Cooperation Agency of the Federal Republic of Germany